2012
DOI: 10.1590/s0103-50532012005000024
|View full text |Cite
|
Sign up to set email alerts
|

An alternative method for the simultaneous determination of copper and lead for quality control of sugar cane spirit using a nanotube-based sensor

Abstract: Um método eletroanalítico foi desenvolvido para determinação simultânea de íons cobre e chumbo em cachaça empregando eletrodo de pasta de carbono modificado com ácido ascórbico e nanotubos de carbono (CPE-AaCNT). A técnica de voltametria de onda quadrada (SWV) com redissolução anódica foi empregada e otimizada com relação aos seguintes parâmetros: frequência (50 Hz), amplitude (100 mV) e incremento de varredura (9 mV). As curvas analíticas apresentaram intervalo linear de 0,09 a 7,00 mg L -1 para o chumbo e pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This voltammogram registered for the mixed 0.2 M copper and 0.03 M lead nitrate solution. In the investigated potential range, two oxidation reactions are occurred on anodic branch and respectively, two typical peaks are clearly revealed at -0.25 V and -0.47 V on cathodic branch, standing for reactions of lead and copper cations reduction: The similar voltammograms with redox reversible couple process for copper and lead are recorded in [13]. Theoretically, lead can also electrodeposited from strongly acidic solutions with a cathodic efficiency approaching 100 % as revealed on CV scans.…”
Section: Feature Of Copper Electrodepositionmentioning
confidence: 55%
“…This voltammogram registered for the mixed 0.2 M copper and 0.03 M lead nitrate solution. In the investigated potential range, two oxidation reactions are occurred on anodic branch and respectively, two typical peaks are clearly revealed at -0.25 V and -0.47 V on cathodic branch, standing for reactions of lead and copper cations reduction: The similar voltammograms with redox reversible couple process for copper and lead are recorded in [13]. Theoretically, lead can also electrodeposited from strongly acidic solutions with a cathodic efficiency approaching 100 % as revealed on CV scans.…”
Section: Feature Of Copper Electrodepositionmentioning
confidence: 55%
“…The parameters of the presented study were compared to those of some previously reported methods [ 7 , 22 , 38 , 39 ]. The technique used, range of quantification, and LODs were compared (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The technique used, range of quantification, and LODs were compared (Table 4 ). The proposed method overperforms those methods under comparison concerning applicability and sensitivity in terms of LOD and linearity range for quantification [ 7 , 22 , 38 , 39 ]. The proposed method was ultrasensitive with higher reliability than other reported methods with an LOD equal to 14.20 ng mL −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing this exposure beyond the 15 mg/day, copper becomes toxic [7]. Excessive intake of copper by humans can cause anemia, liver and kidney damage, and stomach and intestinal irritation [1] as well as diseases such as Wilson, Menkes, MS, Alzheimer, epilepsy, melanoma and rheumatoid arthritis [10]. Furthermore, copper can be phyto- 3,11,12].…”
Section: Introductionmentioning
confidence: 99%